GOLD(I) COMPLEXING IN AQUEOUS SULPHIDE SOLUTIONS TO 500°C AT 500 BAR - Stefánsson A.; Seward T.M. (My University, 2004)
The solubility of gold has been measured in aqueous sulphide solutions from 100 to 500°C at 500 bar in order to determine the stability and stoichiometry of sulphide complexes of gold(I) in hydrothermal solutions. The experiments were carried out in a flow-through system. The solubilities, measured as total dissolved gold, were in the range 3.6 × 10−8 to 6.65 × 10−4 mol kg−1 (0.007–131 mg kg−1), in solutions of total reduced sulphur between 0.0164 and 0.133 mol kg−1, total chloride between 0.000 and 0.240 mol kg−1, total sodium between 0.000 and 0.200 mol kg−1, total dissolved hydrogen between 1.63 × 10−5 and 5.43 × 10−4 mol kg−1 and a corresponding pHT, p of 1.5 to 9.8. A non-linear least squares treatment of the data demonstrates that the solubility of gold in aqueous sulphide solutions is accurately described by the reactions